PP64. CD15S/CD62E HETEROPHILIC INTERACTION MEDIATES ADHESION OF NON-SMALL CELL LUNG CANCER CELLS TO BRAIN ENDOTHELIUM IN LUNG-BRAIN METASTASIS - Pilkington, Prof Geoff (Neuro Oncol, 2017)
INTRODUCTION: More than 50% of patients with lung cancer, including non-small cell lung cancer (NSCLC), will develop brain metastasis which ultimately results in a dismal prognosis. While there are several key steps in the metastastic process, we have focused on the stage where circulating cancer cells adhere to brain endothelium and extravasate through the Blood Brain Barrier (BBB). Sialyl Lewis x, also known as CD15s, is a cell adhesion molecule which is involved in lymphocyte homing and is overexpressed in non-central nervous system cancers. The purpose of our study was to investigate and characterise the interaction of CD15s and TNF-α induced CD62E (E-selectin) in brain metastatic lung cancer cells and brain derived endothelial cells. METHODS: Expression of CD62E and CD15s were evaluated in brain microvascular endothelial cells (hCMEC/D3), primary (A549 and COR-L105) and metastatic NSCLC cells (NCI-H1299, SEBTA-001 and SEBTA-005) using flow cytometry (FC), immunocytochemistry (ICC), immunohistochemistry (IHC) and Western blotting (WB). Qualitative and quantitative adhesion assays adhesion assays under static and physiological flow at shear stress 2.5 dyn/cm2 and volumetric flow rate 10mL/hr were conducted. Immunoblocking of CD15s was performed to investigate its role in adhesion on hCMEC/D3. RESULTS: While CD15s expression on brain endothelial cells was low, CD15s protein expression was detected on primary NSCLC cells, the highest CD15s expression was observed on metastatic NSCLC cells (P<0.001). CD62E expression was observed on hCMEC/D3 cells activated with TNF-α, with lower levels on metastatic NSCLC followed by primary NSCLC cells. Both CD15s and CD62E expression were detected in tissue sections of lung metastatic brain biopsies. Metastatic NSCLC adhered most strongly to hCMEC/D3 compared to primary NSCLC cells. CD15s immunoblocking decreased cancer cell adhesion to brain endothelium under static and shear stress conditions (p<0.001). CONCLUSIONS: This study provides information on the role of CD15s in adhesion of NSCLC cells to brain derived endothelial cells. Our findings suggest that CD15s is involved in the increase in adhesion of circulating lung cancer cells to endothelial cells. Our findings suggests CD15s plays a crucial role in adhesion in concert with TNF-α activation and its binding partner CD62E.